Cutaneous Schwannoma Presenting as a Parotid Tumour - A Case Report and Literature Review: Cutaneous Schwannoma - Jugmohansingh, Gailann; Islam, Shariful; Clarke, John; Mohip, Sharad; Christopher, Marlon; Acco, Oneka (Innovative Journal of Medical and Health Sciences, 2021)
Schwannomas are nerve sheath tumours that can occur at any point along the course of spinal nerves, peripheral nerves and most cranial nerves. The cutaneous schwannoma is uncommon and accounts for 5% of schwannomas. They are slow growing, mostly benign tumours that develop within the dermis of the skin or subcutaneous tissues. Cutaneous schwannomas can be present in the head and neck but growth in the region of parotid gland is not usual and can lead to diagnostic confusion as the parotid gland can also develop schwannomas. We now present the case of a 19 year-old female who presented with a right sided facial mass in the parotid region. Initial tru cut biopsy confirmed the presence of Antoni A and Antoni B type areas with immunochemistry staining positive for S-100. A diagnosis of a parotid schwannoma was made. However, intra-operatively, the mass was found to lie above the superficial musculo-aponeurotic system and a revised diagnosis of a cutaneous schwannoma was made. Observation is the mainstay of treatment. However, surgical resection is performed if the patient has pain, structural dysfunction, cosmetic concerns of if the tumour is malignant. Radiotherapy and chemotherapy have limited roles in management.